Public investment in infrastructure in Latin America: Is debt the culprit - Eduardo Lora (Inter-American Development Bank, Research Department, 2007)
Panel data for seven Latin American countries are used to assess the influence of public indebtedness on public investment in infrastructure in the period 1987-2001. Debt increases are associated with higher public infrastructure investment, an effect that is robust to the inclusion of many other fiscal and macroeconomic variables. This paper also finds some evidence of complementarity between public and private investment and of the negative effect of IMF adjustment loans on infrastructure expenditures. No evidence is found that debt defaults affect public investment in infrastructure.
Keywords: 330; Public investment; Public infrastructure; Public debt; Fiscal policies; Default; Latin America